Automated synthesis of integrated microwave LC-filters layouts with passband losses minimization - V. V. Erokhin; S. A. Zavyalov (Омский научный вестник)
The paper proposes the developed technique for automated synthesis of integrated microwave LC filter layouts with passband losses minimization by minimizing interconnection lengths and searching for optimal layouts of conductors, inductors, and capacitors. Algorithms for minimizing losses and length of LC-filter interconnections are proposed. The layouts of conductors, inductors, and capacitors are optimized based on silicon-verified models that take into account the main characteristics and limitations of the process, skin effect, edge effects, substrate and via influences. The CAD is developed in MathCAD software based on the proposed technique. The use of CAD made it possible to reduce the engineering time for integrated LC-filters to tens of minutes, reduce the filters passband losses by 1,1–2,7 dB and increase the AFCs gain slope by 47–267 dB/dec.